Physicochemical properties and bio‐interfacial interactions of surface modified PDLLA‐PAMAM linear dendritic block copolymers. Issue 19 (28th July 2021) - Simms, Briana L.; Ji, Nan; Chandrasiri, Indika; Zia, Mohammad Farid; Udemgba, Chinwe S.; Kaur, Ravinder; Delcamp, Jared H.; Flynt, Alex; Tan, Chalet; Watkins, Davita L.
Abstract: Here, we demonstrate the applicability of self‐assembling linear‐dendritic block copolymers (LDBCs) and their nanoaggregates possessing varied surfaces as therapeutic nanocarriers. These LDBCs are comprised of a hydrophobic, linear polyester chemically coupled to a hydrophilic dendron polyamidoamine (PAMAM)—the latter of which acts as the surface of the self‐assembled nanoaggregate in aqueous media. To better understand how surface charge density affects the overall operability of these nanomaterials, we modified the nanoaggregate surface to yield cationic (NH3 + ), neutral (OH), and anionic (COO − ) surfaces. The effect of these modifications on the physicochemical properties (i.e., size, morphology, and surface charge density), colloidal stability, and cellular uptake mechanism of the polymeric nanocarrier were investigated. This comparative study demonstrates the viability of nanoaggregates formed from PDLLA‐PAMAM LDBCs to serve as nanocarriers for applications in drug delivery. Abstract :